Interplay Between Charge Accumulation and Oxygen Reduction Catalysis in Nanostructured TiO2 Electrodes Functionalized with a Molecular Catalyst. Issue 14 (5th May 2021) - Kim, Yee‐Seul; Kriegel, Sébastien; Bessmertnykh‐Lemeune, Alla; Harris, Kenneth D.; Limoges, Benoît; Balland, Véronique
Abstract: The catalytic reduction of O2 by a manganese(III) porphyrin immobilized in a nanostructured semiconductive transparent TiO2 electrode is here investigated by UV‐Vis spectroelectrochemistry in an aqueous buffered medium. Analysis of the operando spectroelectrochemical data, collected for both the immobilized catalyst and the TiO2 matrix, demonstrates the coexistence of two faradaic electrochemical processes, namely ( i ) irreversible interfacial electron transfer from TiO2 to the immobilized porphyrin triggering the catalytic reduction of O2, and ( ii ) reversible proton‐coupled electrochemical reduction of TiO2 leading to the accumulation of electrons in the TiO2 bulk. The competition between these two processes is modulated by the local concentration of O2, which itself varies with the rate of the catalysis. Indeed, when O2 is locally strongly depleted by catalysis, the process switches from catalysis to charge storage, like a battery. As a result, the electrons stored in TiO2 were observed to pursue the catalysis even after the electrode polarization was switched‐off ( i. e ., under open circuit). This is an overlooked phenomenon that we believe is important to consider in applications relying on metal oxide‐based photoelectrodes operating in aqueous media. Abstract : Team work : Using UV‐Vis spectroelectrochemistry, we reveal the inter‐dependence of two faradaic processes occurring at nanostructured TiO2 electrodes modified by a manganese porphyrin in an aqueous buffer: (i) the irreversible 4‐electron reduction of O2 to H2 O catalyzed by the molecular catalyst and (ii) the reversible proton‐coupled reduction of the TiO2 matrix.